Deactivation of the JNK Pathway by GSTP1 Is Essential to Maintain Sperm Functionality - Llavanera, Marc; Mateo-Otero, Yentel; Delgado-Bermúdez, Ariadna; Recuero, Sandra; Olives, Samuel; Barranco, Isabel; Yeste, Marc (Frontiers in Cell and Developmental Biology, 2021)
Fifty percent of male subfertility diagnosis are idiopathic and are usually associated to genetic abnormalities or protein dysfunction, which are not detectable through the conventional spermiogram. Glutathione S-transferases (GSTs) are antioxidant enzymes essential for preserving sperm function and maintaining fertilising ability. However, while the role of GSTP1 in cell signalling regulation via inhibition of c-Jun N-terminal kinases (JNK) has been enlightened in somatic cells, it has never been investigated in mammalian spermatozoa. In this regard, a comprehensive approach through immunoblotting, immunofluorescence, computer-assisted sperm assessment (CASA) and flow cytometry analysis was used to characterise the molecular role of GSTP1-JNK heterocomplex in sperm physiology, using the pig as a model. Immunological assessments confirmed the presence and localisation of GSTP1 in sperm cells. The pharmacological dissociation of GSTP1-JNK heterocomplex resulted in the activation of JNK, which led to a significant decrease in sperm viability, motility, mitochondrial activity and plasma membrane stability, as well as to an increase of intracellular superoxides. No effects in intracellular calcium levels and acrosome membrane integrity were observed. In conclusion, the present work has demonstrated, for the first time, the essential role of GSTP1 in deactivating JNK, which is crucial to maintain sperm function, and has also set the grounds to understand the relevance of the GSTP1-JNK heterocomplex for the regulation of mammalian sperm physiology.